Carta al Editor - Lázara Inés La Nuez Cardelle (Universidad de Ciencias Médicas de La Habana, 2014)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <!--[if gte mso 9]> <w:LsdException Locked="false" Priority="64" SemiHidden="false" UnhideWhenUsed="false" N